Neurobiological aspects of social anxiety disorder - Hattingh, Coenraad Jacobus (Department of Psychiatry and Mental Health, 2015)
This thesis investigates the functional neuroanatomy of SAD [Social Anxiety Disorder] using an activation likelihood-estimate meta-analysis (ALE meta-analysis), and explores the structural basis of SAD using a cortical thickness and subcortical gray matter volume analysis.